If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-5X + 5) = -90 Reorder the terms: 3(5 + -5X) = -90 (5 * 3 + -5X * 3) = -90 (15 + -15X) = -90 Solving 15 + -15X = -90 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -15X = -90 + -15 Combine like terms: 15 + -15 = 0 0 + -15X = -90 + -15 -15X = -90 + -15 Combine like terms: -90 + -15 = -105 -15X = -105 Divide each side by '-15'. X = 7 Simplifying X = 7
| 8+4k=40 | | 2/5x1-5/8 | | -4t^2-6t+11=0 | | -2(-X+1)=16 | | 4l+6w=910 | | -2(X-7)=6 | | 2r-3r-1=0 | | 12y^2-10y+2=0 | | 93=3(4x+7) | | -3(2X+2)=48 | | Ln(2x-4)=3.4 | | 7h+3h-3=15 | | x+14+14=x | | .75=4.9t^2+20t | | x-14+14=x | | H-3/5u-9=-5 | | 5x+x-6x=3 | | 4-6(x+1)=6(2x+2) | | r/16=a | | -2*(-5x)= | | -4(-2x-4)=-16 | | .75=-4.9t^2+20t | | 15ab+9a+10b+6=0 | | .5=-4.9t^2+40t+3 | | 7x-3.6=1.3 | | 5z-12z=63 | | 8-5(1+7n)= | | 7(3X+7)=91 | | 20x^2+12x-11=0 | | 7x^2+5x-18=0 | | -7.8-4z-6.5-2z=-5z-5.5 | | 3x^2-7x+2x^2+5x-6= |